2023
DOI: 10.1186/s12893-023-01975-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic proximal gastrectomy with right-sided overlap and single-flap valvuloplasty (ROSF): a case-series study

Abstract: Background There is no standard reconstruction method following proximal gastrectomy, of which gastroesophageal reflux and anastomotic complications are of great concern. Though several techniques have been devised to overcome these postoperative complications, such as double tract reconstruction, double-flap technique and side overlap fundoplication by Yamashita, none of them is considered a perfect solution. Herein, we designed a novel method of esophagogastrostomy after laparoscopic proximal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In addition, the degree of eating discomfort was less severe. In terms of postoperative quality of life, the satisfaction with daily life in the double-channel anastomosis group was better than that in the tubular gastroesophageal anastomosis group[ 33 ]. During the follow-up period, the authors found that esophageal reflux and discomfort after eating had a great impact on the lives of patients, and dual-channel anastomosis effectively reduced the occurrence of these symptoms, which was the same as the conclusion of previous studies[ 34 - 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the degree of eating discomfort was less severe. In terms of postoperative quality of life, the satisfaction with daily life in the double-channel anastomosis group was better than that in the tubular gastroesophageal anastomosis group[ 33 ]. During the follow-up period, the authors found that esophageal reflux and discomfort after eating had a great impact on the lives of patients, and dual-channel anastomosis effectively reduced the occurrence of these symptoms, which was the same as the conclusion of previous studies[ 34 - 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…while factoring in response to PPIs. [ 35 ] Endoscopic findings of erosive inflammation carry high specificity for the condition[ 36 ] but are often absent despite presence of clinically significant GERD. [ 37 ] Multichannel impedance monitoring can be combined to detect non-acid reflux, though its clinical significance remains disputed.…”
Section: Discussionmentioning
confidence: 99%